2015
DOI: 10.1093/ije/dyu277
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic clock is correlated with physical and cognitive fitness in the Lothian Birth Cohort 1936

Abstract: Background: The DNA methylation-based ‘epigenetic clock’ correlates strongly with chronological age, but it is currently unclear what drives individual differences. We examine cross-sectional and longitudinal associations between the epigenetic clock and four mortality-linked markers of physical and mental fitness: lung function, walking speed, grip strength and cognitive ability.Methods: DNA methylation-based age acceleration (residuals of the epigenetic clock estimate regressed on chronological age) were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
441
7
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 518 publications
(476 citation statements)
references
References 29 publications
25
441
7
3
Order By: Relevance
“…This finding is supported by data from Marioni et al (2015b) who find that the Horvath clock underestimates the age in older individuals by approximately 4 years.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This finding is supported by data from Marioni et al (2015b) who find that the Horvath clock underestimates the age in older individuals by approximately 4 years.…”
Section: Discussionsupporting
confidence: 65%
“…To this end, studies are now emerging which demonstrate that an accelerated DNAm age may be linked to disease development. For instance, a modest crosssectional association between accelerated methylation age and lower cognition, weaker grip strength, and poorer lung function was suggested by Marioni et al (2015b), although they could not document that DNAm age at intake could predict future decline in any of the measured parameters. In addition, a significantly accelerated DNAm age of both blood and brain tissue was seen in trisomy 21 individuals, perhaps mirroring the premature aging conditions often experienced by these individuals .…”
Section: Discussionmentioning
confidence: 94%
“…Marioni et al reported significant correlations between the epigenetic clock and cognitive functioning, grip strength and lung function. 46 In addition, Breitling et al showed that the epigenetic clock was correlated with the FI and further confirmed the robustness of this association across diverse domains of health deficits. 45 Our previous study on the relationship between smoking-induced DNA methylation and the epigenetic clock intriguingly found 7 out of the 9 now identified loci to be associated with the epigenetic clock as well, 47 including cg01127300, cg02657160 (CPOX), cg05673882 (POLK), cg07826859 (MYO1G), cg14753356, cg19589396 and cg23667432 (ALPP).…”
Section: Discussionmentioning
confidence: 83%
“…42 Previous studies have evaluated its relationships with 2 other aging estimators, telomere length, 43,44 and age-related DNA methylation changes ("epigenetic clock"). 45,46 Telomere length was not associated with frailty, neither in Asian nor in Caucasian populations. 43,44 In contrast, the epigenetic clock was found to be significantly associated with frailty-related phenotypes and the FI.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, obesity altered the epigenetic clock of the liver but not for any other tissue sites (11). Acceleration of this clock has functional implications, as age-accelerated DNAm correlates with poorer performance on physical and mental aptitude tests and higher overall mortality, even after adjusting for known risk factors (14,15). Thus, the Horvath clock can be assayed from peripheral blood, demonstrates concordance with tissue DNAm, and can be used to calculate accelerated aging to provide prognostic information.…”
Section: Introductionmentioning
confidence: 99%